Penerapan Media audio visual dalam meningkatkan konsentrasi anak membaca doa sebelum belajar di TK Muslimat NU 1 Pamekasan. - Kholifatur Rohmah; Latifatun Nabila; Dea Ramadhani; Nurul Ismaiyah; Zainah (LPPM STAI La Tansa Mashiro, 2025)
This study aims to improve children's concentration skills through audio-visual media. This study uses the classroom action research (CAR) method with a pre-cycle to determine the initial conditions before the touch of audio-visual media is carried out in 2 cycles, cycle I of 3 actions and cycle II of 2 actions. The stages in this study start from planning, implementation, observation, and reflection. Data collection techniques in this study include observation, interviews, and documentation, data validation used is comparing data sources. Data analysis uses a conclusion drawing technique, namely a qualitative data analysis method to identify patterns in data. The results of the study showed that the application of audio-visual media in prayer reading activities before studying can improve children's concentration skills in Group A of Muslimat NU 1 Pamekasan Kindergarten.